Redesign of the Aeration Centrifugal Fan Impeller in a Steam Power Plant to Reduce Vibration Issues - Dadang Almadi; Mohammad Alexin Putra; Muhammad Fuad Abdul Hakim (G-Tech: Jurnal Teknologi Terapan, 2025)
The aeration centrifugal fan (ACF) functions to inject pressurized air into the aeration pond containing wastewater from power plant operations. This increases the water's oxygen content before discharge. However, as a rotating device, the ACF often faces high vibration issues, including at a steam power plant in Cilacap Regency. Vibration in this unit exceeded permissible limits. Analysis identified blade pass and surging, linked to the impeller design, as the cause. This indicates the existing impeller was not suited to actual operational conditions. This study aims to redesign the impeller to reduce vibration. The redesign involved increasing the number and width of blades, followed by CFD simulations and vibration testing. Results showed volumetric flow rate and pressure increased from 50,887.1 m³/s to 61,185 m³/s and from 226.9 kPa to 696.3 kPa. Vibration dropped from 19.96 mm/s to 2.916 mm/s (below the 7.1 mm/s limit). Thus, the redesign successfully reduced excessive vibration.